Praktik Pengenalan Lapangan terhadap Observasi Fisik di RA Al-Fajar Kec. Medan Denai Kab. Deli Serdang - Mungkur, Ainun Qalbu Ramadhani; Lubis, Ainun Ramdhani; Harahap, Nurul Hafifah; Aminah, Siti; Lutfhi, Mukhyar; Marpaung, Zulham Efendi; Ketaren, Yogi Karmelta (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This article discusses the practice of field recognition of physical observation at RA Al-Fajar. This school is located in a strategic location to support the creation of good teaching and learning activities. RA Al-Fajar is a school that really maintains cleanliness, neatness, and order in carrying out administration in the learning process. There are six teachers at RA Al-Fajar, while eleven students are available only in one class. The facilities and infrastructure at this school are very decent and good. The learning and teaching activities also in accordance with the education units based on the Permendiknas, namely using the learning implementation plan. This research aims to determine the conditions and circumstances that occured at RA Al-Fajar regarding infrastructure and teaching and learning activities. The method in this study is a qualitative research method with observation data collection instruments. The results of this study RA Al-Fajar is a school with magnificient infrastructure, teaching, and learning activities. The infrastructure provided is in accordance with the learning needs of children. The curriculum is implement in accordance with PERMENDIKBUD standards. As well as teaching and learning activities are also in accordance with the standards of the learning process.